BANDUNG’s POLITICAL AND YOUTH ENGAGEMENT IN THE DIGITAL SPHERE - Muradi, Muradi; Silas, Jonah (Universitas Padjadjaran, 2024)
The development of political information media has progressed very rapidly. This research tries to explore and measure the political literacy and political participation of young people in Bandung City. The theory then used is cyberdemocracy to see the development of information space. The article uses a qualitative method based on library research to collect and analyze data from various literature sources, complemented by survey results from IPRC, to explore Cyberdemocracy theory and its application to social realities in Bandung City. The results show that the level of political literacy and political participation of the younger generation in Bandung City towards political information is still low. The results show that the advancement of information media only goes linearly with the increase in political literacy and political participation in virtual public spaces. As many as 42.3% of young people in Bandung City have been exposed to doubtful news or information. Exposure in this context is like receiving, reading, or even spreading information that is still doubtful and 52.4% have never expressed an opinion about political issues on digital sphere.